Effectiveness of wildlife guards at access roads - Tiffany D. H. Allen; Marcel P. Huijser; David W. Willey (Wildlife Society Bulletin, 2013)
Abstract The reconstruction of 90.6 km of U.S. Highway 93 from Evaro to Polson, Montana, USA, includes 41 wildlife crossing structures and 13.4 km of road with wildlife fencing. These measures are aimed at reducing wildlife–vehicle collisions and increasing human safety, while allowing wildlife to traverse the landscape. In the fenced road sections, gaps in the fence for side roads are mitigated by wildlife guards (similar to cattle guards). We monitored wildlife movements with cameras for 2 years from mid‐July 2008 to mid‐July 2010 at 2 wildlife guards and in 1 large crossing structure adjacent to one of the wildlife guards. We investigated how effective these wildlife guards were as a barrier to deer (Odocoileus spp.), black bear (Ursus americanus), and coyotes (Canis latrans). We also compared movements across a wildlife guard with movements through an adjacent crossing structure. The wildlife guards were ≥85% effective in keeping deer from accessing the road and 93.5% of deer used the crossing structure instead of the adjacent wildlife guard when crossing the road. The wildlife guards were less effective in keeping black bear and coyotes from accessing the road (33–55%). However, all black bears and 94.7% of coyotes used the crossing structure instead of the adjacent wildlife guard when crossing the road. Though the wildlife guards were not an absolute barrier to these species, the results indicate wildlife guards are a substantial barrier to deer and can be considered effective in mitigating gaps in a fence at access roads for these species. © 2013 The Wildlife Society.